Effects of thermal plasma surface hardening on wear and damage properties of rail steel. (July 2018) - Xiang, Yong; Yu, Deping; Cao, Xiuquan; Liu, Yang; Yao, Jin
The aim of this study is to investigate the effects of thermal plasma surface hardening on wear and damage properties of rail steel. Wear tests of the rail steel treated by thermal plasma jet and untreated one were carried out on a block-on-ring wear test machine. Their corresponding wear and damage properties were contrasted. Results indicate that the microstructure of the heat-affected zone of the rail steel treated by thermal plasma surface hardening was transformed. It mainly consists of lath and acicular martensite and also small amount of sorbite, bainite, and retained austenite. As a result, the thermal plasma surface hardening effectively improves the wear resistance of the rail steel. The main wear mechanism of the treated rail steel is mild plowing wear, while that of the untreated rail steel is a combination of severe plowing wear and adhesion wear. Therefore, it is verified that thermal plasma surface hardening is effective in improving the wear resistance, alleviating the surface damage and thus prolonging the service life of the rail steel.